1978
DOI: 10.1007/bf01809225
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of the coagulatory system in patients with severe cerebral trauma. I

Abstract: This is an investigation into thromboplastin time, partial thromboplastin time, plasma thrombin time, fibrinogen, and platelets in 30 patients with severe brain injury over 7--14 days. Platelets showed a very marked initial decrease and a slow return to normal around the seventh day. Fibrinogen was initially lowered in most of the cases, and raised from the second day onward. Changes in the other laboratory values were less definite. Latent signs of consumption coagulopathy were not accompanied by bleeding dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Some degree of coagulopathy has been reported in 15 to 35% of all TBIs 11,18,35 and in more than 60% of patients with severe TBI. 3,7,15 It has been estimated that 15 to 40% of patients with severe TBI have full-blown DIC. 6,15,26,35 These changes in blood coagulation probably reflect the cerebral IC process; studying them may allow us to assess the degree of IC and to monitor its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some degree of coagulopathy has been reported in 15 to 35% of all TBIs 11,18,35 and in more than 60% of patients with severe TBI. 3,7,15 It has been estimated that 15 to 40% of patients with severe TBI have full-blown DIC. 6,15,26,35 These changes in blood coagulation probably reflect the cerebral IC process; studying them may allow us to assess the degree of IC and to monitor its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…who also reported the prolongation of TT following head injury;[19] although, Auer L in his study on thirty patients did not find any significant changes in thrombin time. [20]…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the results of Kumara et al . [24] and other,[2023] who have reported that coagulopathy is predictor for poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were then that occur in some patients with isolated head trauma. [11][12][13][14][15][16][17][18][19][20][21][22] transferred to the intensive care unit and from there to the Decreased levels of antithrombin (AT), fibrinogen and protein C neurosurgery ward.…”
Section: Discussionmentioning
confidence: 99%